SEO AND SEM BENEFITS IN DIGITAL MARKETING - Baltiņš, Viesturs; Zarembo, Imants (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The paper deals with the search engine optimization and search engine marketing benefits to website. Explains the differences as well as their similarities between SEO and SEM. Gives tips on what conditions one of the strategies is preferable to boost website ratings than the other, and under what circumstances it is more effective to use both SEO and SEM strategies.